2020
DOI: 10.1101/2020.04.29.20084863
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inflammatory markers in Covid-19 Patients: a systematic review and meta-analysis

Abstract: Introduction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…More studies have also reported that a significant increase in WBC presents a clinical worsening sign that has been shown to be significantly elevated in dead subjects (Henry et al, 2020). However, another study has found normal WBC values with lymphocyte decrease in diagnosed COVID-19 patients (Golnaz et al, 2020).…”
Section: Discussionmentioning
confidence: 91%
“…More studies have also reported that a significant increase in WBC presents a clinical worsening sign that has been shown to be significantly elevated in dead subjects (Henry et al, 2020). However, another study has found normal WBC values with lymphocyte decrease in diagnosed COVID-19 patients (Golnaz et al, 2020).…”
Section: Discussionmentioning
confidence: 91%
“…One study demonstrated normal WBC count accompanied by lymphopenia. 70 Prolonged PT 41,71 or elevated D-dimer/FDP [67][68][69]71 represented derangements in the coagulation profile. Elevated inflammatory markers-CRP, 24,65,66,68,69,72,73 ferritin, 64,72,73 procalcitonin, 24,66 SAA, 69,72 and IL-6 64,67,69,72 -and other biomarkers-LDH, 24,66-69 CK, 24 CK-MB, 67 AST/ ALT, 24,41,66,67 bilirubin, 24,74 BUN, 67,69 and creatinine 67,69were also among significant findings.…”
Section: Summary Of Selected Systematic Reviews With or Without Meta-...mentioning
confidence: 99%
“…In COVID-19 patients, the release of pro-inflammatory cytokines causes active inflammation, which damages the lungs. 17 The alteration of inflammatory markers in COVID-19 patients can be a good indicator to consider when finding these patients.…”
mentioning
confidence: 99%